2021
DOI: 10.1097/j.pain.0000000000002209
|View full text |Cite
|
Sign up to set email alerts
|

Assessing outcome in postoperative pain trials: are we missing the point? A systematic review of pain-related outcome domains reported in studies early after total knee arthroplasty

Abstract: The management of acute postoperative pain remains suboptimal. Systematic reviews and Cochrane analysis can assist with collating evidence about treatment efficacy, but the results are limited in part by heterogeneity of endpoints in clinical trials. In addition, the chosen endpoints may not be entirely clinically relevant. To investigate the endpoints assessed in perioperative pain trials, we performed a systematic literature review on outcome domains assessing effectiveness of acute pain interventions in tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 289 publications
2
10
0
Order By: Relevance
“…The point you raised in your letter was an (in your view) missing outcome domain, namely, “opioid consumption.” We agree that this outcome domain is used very frequently in postoperative pain effectiveness and efficacy trials; as shown by us in our systematic literature research on domains assessed in pain studies after TKA and sternotomy, 1,5 analgesic consumption (as an umbrella term for opioid or analgesic consumption or rescue analgesia, among others) was the second most assessed outcome domain (assessed by more than 80% of the studies). The domain analgesic consumption was therefore certainly discussed by the panel during the consensus face-to-face meeting.…”
Section: Letter To the Editorsupporting
confidence: 56%
See 2 more Smart Citations
“…The point you raised in your letter was an (in your view) missing outcome domain, namely, “opioid consumption.” We agree that this outcome domain is used very frequently in postoperative pain effectiveness and efficacy trials; as shown by us in our systematic literature research on domains assessed in pain studies after TKA and sternotomy, 1,5 analgesic consumption (as an umbrella term for opioid or analgesic consumption or rescue analgesia, among others) was the second most assessed outcome domain (assessed by more than 80% of the studies). The domain analgesic consumption was therefore certainly discussed by the panel during the consensus face-to-face meeting.…”
Section: Letter To the Editorsupporting
confidence: 56%
“…We are grateful for the letter from Karlsen et al, 4 that raised a very interesting point related to our previously published articles in PAIN. 1,6 Within these articles (and another one published recently by us as well 5 ), we systematically investigate outcome domains assessed in prospective interventional clinical trials regarding pain management after total knee arthroscopy (TKA 1 ) and sternotomy. 5 These data were consecutively used to develop a Core Outcome Set (COS) of domains referring to perioperative pain management after surgery in clinical trials, observational studies, and clinical practice by involving all relevant stakeholders, including patients.…”
Section: Letter To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the Delphi process by Pogatski et al did not include representatives from sites in North or South America or Asia, although a major portion of analgesic trials is conducted there. 1,4 In recent years, the United States has focused on the opioid crisis, and had Americans been included in the Delphi process, the consensual core outcome set may have looked different. Third, Bigalke et al state that “analgesic consumption varies widely between patients without showing a clear association to the quality of pain management” with reference to a cross-sectional study investigating the association between pain intensity and desire for opioids.…”
Section: Letter To the Editormentioning
confidence: 99%
“…We read with interest the article by Bigalke et al, 1 which is a review of reported outcomes in 295 trials on postoperative pain management after total knee arthroplasty. Along with 3 similar reviews on other types of surgery, this formed the list of potential outcomes in a subsequent Delphi process by Pogatski-Zahn et al, 5 leading to a core outcome set in postoperative pain management.…”
Section: Letter To the Editormentioning
confidence: 99%